Understanding CO2 Emissions from the Global Energy Sector - Foster, Vivien; Bedrosyan, Daron (World Bank, Washington, DC, 2014)
The energy sector contributes about 40 percent of global emissions of CO2. Threequarters of those emissions come from six major economies. Although coal-fired plants account for just 40 percent of world energy production, they were responsible for more than 70 percent of energy-sector emissions in 2010. Despite improvements in some countries, the global CO2 emission factor for energy generation has hardly changed over the last 20 years.